Metagenomics and conventional analyses of bacterial diversity in selected sites of Putrajaya Lake, Malaysia - Mat Lazim, Nurul Najwa Farihah (2020)
The anthropogenic activities will give impact to the water quality and bacterial diversity in a freshwater lake. The abundance and diversity of bacteria were determined through Illumina Miseq Sequencing as well as through bacterial identification on enrichment media. The physico-chemical parameters were analyzed to determine the water quality and to assess their relation to the bacterial community. Triplicate water samples were collected from Putrajaya Lake at three different sites monthly from November 2017 to January 2018 and from May 2018 to August 2018. The metagenomics analysis revealed that a total of 46 phyla, 276 classes, 460 order, 460 families, 765 genera and selected bacteria species were identified. Proteobacteria represented most abundant Phylum (6.49%) throughout the dry and wet seasons, followed by Actinobacteria (2.95%), Bacteroidetes (2.86%), Verrucomicrobia (1.74%), Cyanobacteria (1.48%), Planctomycetes (1.34%), Firmicutes (0.52%), Chloroflexi (0.34%), Chlamydiae (0.14%) and Acidobacteria (0.09%). Through culture studies, a limited number of bacteria were identified which include these 6 genera; Acinetobacter, Enterobacter, Bacillus, Pseudomonas, Lysinibacillus and Staphylococcus. Phylogenetic analysis using clustered Neighbour Joining method showed that there were 23 phylotypes which were classified into two phyla; Firmicutes and Proteobacteria. The Pearson Correlation Coefficient and Canonical Correspondence Analysis showed that the species composition of bacteria at each site was influenced by physico-chemical parameters (e.g., phosphate, nitrate, ammonia-nitrogen, pH) and tropical climate conditions of the lake. The study demonstrates that the lake has a multitude of bacterial communities shown at three different sampling sites that are associated with physico-chemical parameters. The dominant phyla; Proteobacteria are important decomposers in lake sediments. The wetlands of Putrajaya plays a great role as a filtration system to remediate the chemical content of water into Putrajaya Lake as well as acts as an important source of influence to a balanced bacterial diversity of the lake.